2020
DOI: 10.1039/d0cp03138k
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanism of ionic liquid-induced protein unfolding

Abstract: Ionic liquids (ILs) are gaining attention as protein stabilizers and refolding additives. However, varying degrees of success with this approach motivates the need to better understand fundamental IL-protein interactions. A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Several studies revealed the contribution of both IL cation and anion in the thermal destabilization of proteins (Figueiredo et al 2013;Bui-Le et al 2020;Hebal et al 2020;Singh et al 2020). This destabilization is a result of the direct interaction of ions to the protein, but regarding protein stability, there is a dominating effect of anion over cation (Figueiredo et al 2013;Okur et al 2013;Bui-Le et al 2020).…”
Section: Effect Of Ils On Stability Of Thermostable Glycoside Hydrolasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies revealed the contribution of both IL cation and anion in the thermal destabilization of proteins (Figueiredo et al 2013;Bui-Le et al 2020;Hebal et al 2020;Singh et al 2020). This destabilization is a result of the direct interaction of ions to the protein, but regarding protein stability, there is a dominating effect of anion over cation (Figueiredo et al 2013;Okur et al 2013;Bui-Le et al 2020).…”
Section: Effect Of Ils On Stability Of Thermostable Glycoside Hydrolasesmentioning
confidence: 99%
“…In a study of the thermal destabilization of lysozyme in the presence of two imidazolium-based ILs, [EMIM]EtSO 4 and [EMIM]Et 2 PO 4 , Singh et al (2020) observed that in both IL systems, positive protein residues attract anion and negative protein residues attract cation. In addition, some hydrophobic residues on the protein surface also attract hydrophobic parts of both cation and anion.…”
Section: Effect Of Ils On Stability Of Thermostable Glycoside Hydrolasesmentioning
confidence: 99%
See 1 more Smart Citation
“…), ionic liquids (ILs) have rapidly established themselves in the field of bioanalytical protein chemistry during the last two decades. 30 33 Using these new green solvents to perform protein detection has received much attention, in particular for identifying the low-abundance analytes in biological samples. 34 , 35 Previous works have mainly focused on using ILs as surface modifiers (i.e., ILs-functionalized or modified substrates) to improve the sensitivity and the limit of detection, 36 , 37 in which the modification process is usually complex.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al, 2020). The destabilizing power of [emim][EtSO 4 ] and [emim][Et 2 PO 4 ] was higher than that of a strong denaturant as observed from lowering in the T…”
mentioning
confidence: 99%